Venture capital market as a place of meeting the financial needs of enterprises in the bioeconomy sector - Konrad, Szydłowski; Szturo, Marek (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The paper aims to characterization and diagnosis of the venture capital market and to determine its importance in the process of financing of bioenterprises. The followingresearch hypothesis was formulated: the growing importance of the bioeconomy sector in Poland in conjunction with the high investment risk, indicate a high potential for the development of the venture capital market in the area of financing bioenterprises.The theoretical part of the the paper presents the concept and importance of the bioeconomy, basic conditions for the development of this sector, and identifies main barriers to accessibility bioenterprises to sources of capital. The characteristic of PE/VC funds was presented as well. Results of investment activity of funds was presented in the empirical part of the paper. A size and a structure of investment were analysed with particular reference to the trade and the development phase of the enterprises. The analysis was based on the data published by the European Venture Capital Assotiation.Results of the analysis indicated the growing importance of PE/VC funds in the financing of the development of bioenterprises. However the scope of their activity is still relatively little, what is confirmed bythe small amount of funds invested in the bioeconomy sector.In the future the venture capital market should be important source of financing of the bioeconomy sector in Poland.